2015
DOI: 10.5551/jat.25718
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Circulating Total Osteocalcin Level and the Development of Cardiovascular Disease in Middle-aged Men: A Mean 8.7-year Longitudinal Follow-up Study

Abstract: Aim: Recent studies have suggested that the serum osteocalcin level is associated with various cardiovascular risk factors. The aim of this study was to determine whether the serum total osteocalcin level is associated with the development of cardiovascular disease (CVD). Methods: A total of 1,290 men 40-78 years of age were enrolled. The subjects were followed regularly at the Health Promotion Center on an outpatient basis and during hospitalization for a mean of 8.7 years, and the incidence of CVD (coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
1
22
2
3
Order By: Relevance
“…Thus, a follow-up study of 1290 Korean men found that the serum osteocalcin level was not associated with the development of CVD, even after adjustment for other risk factors for CVD [29]. Another 4.1-year follow-up study also reported no association between plasma osteocalcin level and CVD in younger-old subjects (65–74 years) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a follow-up study of 1290 Korean men found that the serum osteocalcin level was not associated with the development of CVD, even after adjustment for other risk factors for CVD [29]. Another 4.1-year follow-up study also reported no association between plasma osteocalcin level and CVD in younger-old subjects (65–74 years) [13].…”
Section: Discussionmentioning
confidence: 99%
“…[10] Similarly, a cross-sectional study has reported that osteocalcin concentration in postmenopausal women was positively correlated with the prevalence of coronary atherosclerosis, contrary to the results of previous studies. [27] There has also been a report that in both healthy men and premenopausal and postmenopausal women, osteocalcin has no independent correlation with the carotid intima-media thickness.…”
Section: Discussionmentioning
confidence: 97%
“…[6789] Although these studies have shown that osteocalcin concentration in the blood may be independently correlated with increased risk of cardiovascular diseases, the results lack consistency; there have been other reports suggesting no relation of osteocalcin to the incidence of cardiovascular diseases. [10]…”
Section: Introductionmentioning
confidence: 99%
“…However, not all cohort studies have found a significant relationship between serum osteocalcin levels and the incidence of cardiovascular events. A longitudinal follow‐up study in Korea with a mean follow‐up period of 8.7 years found that serum osteocalcin levels were not associated with the development of CAD in 1290 middle‐aged and elderly men (40‐78 years) . Holvik et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have not yet provided consistent conclusions regarding the associations between serum osteocalcin levels and CAD morbidity and mortality. This is perhaps because of the differences in populations or races, serum osteocalcin measurement, and the diagnostic criteria for CAD …”
Section: Introductionmentioning
confidence: 99%